2018
DOI: 10.1053/j.gastro.2018.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Tight Junction Protein Claudin 18 Promotes Progressive Neoplasia Development in Mouse Stomach

Abstract: H pylori infection of B6:129 mice reduced the expression of CLDN18 early in gastric cancer progression, similar to previous observations from human gastric tissues. CLDN18 regulates cell lineage differentiation and cellular signaling in mouse stomach; CLDN18-knockout mice develop intraepithelial neoplasia and then large and focally dysplastic polypoid tumors in the absence of H pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 66 publications
6
87
0
Order By: Relevance
“…To date, little is known about the clinical impact of CLDN18.2 expression in metastatic GC. Previous studies have suggested that loss of CLDN18.2 expression is associated with an increased proliferative and invasive potential of GC [21,22]. We found that CLDN18.2 and E-cadherin expression was decreased in patients with PM compared to those without PM.…”
Section: Discussionsupporting
confidence: 45%
“…To date, little is known about the clinical impact of CLDN18.2 expression in metastatic GC. Previous studies have suggested that loss of CLDN18.2 expression is associated with an increased proliferative and invasive potential of GC [21,22]. We found that CLDN18.2 and E-cadherin expression was decreased in patients with PM compared to those without PM.…”
Section: Discussionsupporting
confidence: 45%
“…Moreover, IM was confirmed by overexpression of MUC2, and by finding Alcian blue/Periodic Acid-Schiff-stained cells at the surface and base of gland ( Figure 3E). These results demonstrated that Slc26a9 KM aged 6 months exhibited robust expression levels of the markers for chronic atrophic gastric, metaplasia, mucosal barrier defect and dysplasia that were also found in human GC [12]. Based on gene microarray analyses, known oncogenes in GC, including ErbB2, Cdkn2a, MAX, TERT, K-Ras, N-Ras, Cyclin E, c-Met and FGFR2, were upregulated at 14 months of age, whereas tumor suppressors, P53, CDH1, and APC, were downregulated ( Figure 3A).…”
Section: Identification Of Molecular Markers For Atrophy Spem Im Mmentioning
confidence: 60%
“…Furthermore, Slc26a9 deletion leaded to the alteration of multiple signaling pathways that are related to the regulation of cell proliferation, apoptosis, and differentiation, as well as barrier integrity. Emerging evidence suggests that activation of Wnt signaling pathway can be linked to GC development and progression [12,38]. Activation of the Wnt pathway is known to result in β-catenin nuclear accumulation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of epithelial integrity by disruption of cell‐cell junctions mediated by H pylori may also contribute to gastric carcinogenesis. Hagen et al showed that H pylori infection induces attenuation/loss of the tight junction protein Claudin‐18 in the stomach of mice. Deletion of Claudin‐18 in these animals led to the activation of multiple signaling pathways involved in cell proliferation and cancer stem cell development, to increased inflammation, and to the appearance of gastric intraepithelial neoplasia and tumorigenesis.…”
Section: Microbial Agents In Gastric Cancermentioning
confidence: 99%